COVID-19 and Hypertension: The What, the Why, and the How - Muhamad, Shah-Abas; Ugusman, Azizah; Kumar, Jaya; Skiba, Dominik; Hamid, Adila A.; Aminuddin, Amilia (Frontiers in Physiology, 2021)
It has been a year since the coronavirus disease 2019 (COVID-19) was declared pandemic and wreak havoc worldwide. Despite meticulous research has been done in this period, there are still much to be learn from this novel coronavirus. Globally, observational studies have seen that majority of the patients with COVID-19 have preexisting hypertension. This raises the question about the possible relationship between COVID-19 and hypertension. This review summarizes the current understanding of the link between hypertension and COVID-19 and its underlying mechanisms.